Operation Pied Piper : the wartime evacuation of schoolchildren from London and Berlin, 1938-46 - Gärtner, Niko (Emerald Publishing Limited : Information Age Pub., 2012)
When war came, the authorities in London and Berlin operated evacuation schemes that sent children into billets and camps in rural reception areas. The children's exodus either happened orderly and followed years of planning and discussion amongst policy makers (London), or haphazardly following the sudden realization that the war would not be fought exclusively elsewhere (Berlin). As policies, the government evacuation schemes were bold, controversial and - considering their distinct political contexts - surprisingly similar; as were some of their consequences: the recipients did not accept them uncritically, the municipalities failed to evacuate the majority of children from the cities under attack, and private provision catered for a lot more children than the official schemes.This study of the British evacuation and Third Reich Kinderlandverschickung is an original and important contribution to the existing scholarship in two ways. First, it stays in the cities (rather than leaving with the evacuees towards the already well-researched evacuation experience) in order to show the scheme' geneses, but also to appreciate issues related to their operational conduct in the face of stray children, closed schools and rebellious parents in town. Second, the study explores the evacuation schemes in the two warring capitals in comparative perspective, thus critically analyzing how policy was developed and executed in the face of shifting and differing political contexts and acute sociological challenges. This study traces local developments through sources, from the earliest plans contemplated in London during the 1930s to the collapse of the Third Reich and delayed return of Berlin children in 1946. It covers operational aspects and explores themes of agency, citizenship, childhood, schooling and the relationship between state and individual.The robust historical research, combined with a strong central narrative, should appeal not only to historians of education or military historians, but also to policy makers, educators, former evacuees and all readers with a private or professional interest in wartime childhoods and evacuations.